Serum CCL20: A novel potential marker of cardiovascular risk in alopecia areata patients - Ahmed M Hamed; Amal M Abdelmaksoud; Asmaa A Elfallah; Enas M Sweed; Samah E Ibrahim (Wolters Kluwer Medknow Publications, 2023)
Background Alopecia areata (AA) is a prevalent autoimmune skin disease that may be associated with systemic disorders. The connection between cardiovascular risks and AA is not widely investigated. Chemokine (C-C motif) ligand 20 (CCL20) has been found to be related to cardiovascular comorbidities. Objective To investigate the role of CCL20 in AA patients and its relation to cardiovascular comorbidity. Patients and methods This study enrolled 80 AA patients and 40 age and sex-matched control subjects. Serums CCL20, high sensitive C- reactive protein (Hs-CRP), lipid profile in addition to carotid intima-media thickness (CIMT) were investigated in all subjects. Results AA patients expressed significantly higher serum CCL20 levels than healthy controls (29.6±20.4 vs. 10.3±6.7, P <0.001). Serum CCL20 was significantly correlated with total cholesterol (TC), low-density lipoprotein (LDL), triglycerides (TGs), and CIMT (p value: 0.002, 0.044, <0.001, <0.001, respectively). Regression analysis was conducted for prediction of CV increased risk and revealed that older age, higher LDL, TC, TG, HS-CRP, CCL2, lower HDL and presence of alopecia were associated with risk of higher CIMT in univariable analysis. Conclusion Serum CCL20 might have a role in AA pathogenesis. It may serve a new possible link between AA and both systemic inflammation and cardiovascular risk observed in AA patients.